Opini Audit dan Kinerja Keuangan Pemerintah Daerah dengan Realisasi PAD sebagai Pemediasi - Dwi Pradnyani, Ni Made; Sri Harta Mimba, Ni Putu (E-Jurnal Akuntansi, 2020)
The purpose this study was determine effect of audit opinion on the financial performance District / City Governments in Bali Province with local revenue as mediator based on legitimacy theory. This research was conducted at Provincial Government of Bali in 2013-2017 using the saturated sample method. Data analysis technique used path analysis. Analysis found that audit opinion had a positive effect on local own-source revenue. Shows that good audit opinion tends to increase the resources provided by local community specifically regional original income. Audit opinion has positive effect on the financial performance of District / City Governments in Bali Province in 2013-2017. Realization PAD has positive effect on financial performance of District / City Governments in Bali Province in 2013-2017. The realization of regional own-source revenue mediating variable in the relationship between audit opinion and local government financial performance. Keywords: Audit Opinion; Local Revenue; Local Government Financial Performance.